Knowledge on Uterine Prolapse among Reproductive Age Women Attending Tertiary Level Hospital, Chitwan - Paudel, Madhu Maya; Bhusal , Mina Kumari; Regmi , Kamala; Chaudhary, Tulasi (Journal of Bharatpur Hospital, 2025)
Background Uterine prolapse is a prevalent health issue affecting women’s reproductive health, mostly in developing countries like Nepal. Knowledge on Uterine prolapse among reproductive-age women is essential to prevent the reproductive health related complications. The objective of the study was to determine the level of knowledge on uterine prolapse among married women of reproductive age (MWRA). MethodsA descriptive cross-sectional study was conducted among 273 married women of reproductive age attending obstetric and gynecological outpatient department (OPD) at Bharatpur Hospital. Data was collected from July 15 to August 15, 2025 by using a structured interview schedule. Data was analyzed using descriptive and inferential statistics like frequency, percentage, mean, standard deviation, chi-square and fisher exact test. ResultsThe study revealed that all the respondents heard about uterine prolapse. Regarding overall knowledge on uterine prolapse, more than half (52.4%) of the respondents has moderate level of knowledge, 38.5% had low level of knowledge and only 9.2% had a high level of knowledge. Among different variables, the level of knowledge on uterine prolapse was statistically significant with ethnicity, level of education and age at marriage. Conclusions The finding of the study concludes that good knowledge on uterine prolapse is essential to prevent reproductive health related problems. All the respondents heard about uterine prolapse, however, overall knowledge was low. So, health awareness and education programs focusing on prevention measures are essential for improving the different aspects of knowledge regarding uterine prolapse.